2003
DOI: 10.1091/mbc.e02-07-0400
|View full text |Cite
|
Sign up to set email alerts
|

Gef1p, a New Guanine Nucleotide Exchange Factor for Cdc42p, Regulates Polarity inSchizosaccharomyces pombe

Abstract: Schizosaccharomyces pombe cdc42+regulates cell morphology and polarization of the actin cytoskeleton. Scd1p/Ral1p is the only described guanine nucleotide exchange factor (GEF) for Cdc42p in S. pombe. We have identified a new GEF, named Gef1p, specifically regulating Cdc42p. Gef1p binds to inactive Cdc42p but not to other Rho GTPases in two-hybrid assays. Overexpression of gef1+increases specifically the GTP-bound Cdc42p, and Gef1p is capable of stimulating guanine nucleotide exchange of Cdc42p in vitro. Overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
154
0
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(170 citation statements)
references
References 50 publications
7
154
0
9
Order By: Relevance
“…However, previous reports have shown that while gef1Δ mutants are mainly monopolar, about 40% of interphase cells show bipolar growth ( Figure 5B) (Coll et al, 2003;Das et al, 2012;Das et al, 2015). If Gef1 is required for Scd1 localization to the new end, how does bipolar growth occur in some gef1Δ cells?…”
Section: Gef1 Establishes Polarized Growth At a Nascent Sitementioning
confidence: 87%
See 4 more Smart Citations
“…However, previous reports have shown that while gef1Δ mutants are mainly monopolar, about 40% of interphase cells show bipolar growth ( Figure 5B) (Coll et al, 2003;Das et al, 2012;Das et al, 2015). If Gef1 is required for Scd1 localization to the new end, how does bipolar growth occur in some gef1Δ cells?…”
Section: Gef1 Establishes Polarized Growth At a Nascent Sitementioning
confidence: 87%
“…Thus, we asked whether a similar interaction occurs at sites of polarized growth. Gef1 promotes bipolar growth in fission yeast (Coll et al, 2003;Das et al, 2012). Cells lacking gef1 show increased monopolarity, with polarized growth only occurring at the old end.…”
Section: Gef1 Is Required For Bipolar Scd1 Localizationmentioning
confidence: 99%
See 3 more Smart Citations